Shaping the biology of emotion: Emovere, an interactive performance. Issue 1 (2nd January 2019) - Jaimovich, Javier; Morand, Francisca
ABSTRACT: This paper presents the artistic creation and research work developed for the piece Emovere (2015), an interactive dance and sound performance. Emovere 's creation process focused on configuring artistic material by exploring the biology of emotion in association with physiological signals and the induction of emotional states based on corporeal patterns. The composition methodology drew from a creative interdisciplinary laboratory that used Alba Emoting and interactive technologies with biosensors to generate artistic material. Four designs that propose a relationship between the performers' bodies and an interactive-sound environment are presented and discussed in order to illustrate an artistic interdisciplinary approach that reflects on the biology of emotion.